2015
DOI: 10.1007/s10900-015-9996-1
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Cervical Cancer Screening in Rural Kenya: Perspectives from a Provider Survey

Abstract: Although cervical cancer is highly preventable through screening, it remains the number one cause of cancer-related death in Kenyan women due to lack of funding and infrastructure for prevention programs. In 2012, Family AIDS Care and Education Services in partnership with the Kenya Ministry of Health began offering free screening at eleven rural health facilities. We sought to explore why screening coverage remains low at some sites. We examined the barriers to screening through a survey of 106 healthcare sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
56
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 13 publications
2
56
0
Order By: Relevance
“…The providers cited a lack of confidence due to limited training in screening and treatment of precancerous lesions. These findings are not unique and have been found in surveys of health care providers in similar environments such as Kenya . In addition, limited space and equipment hampered attempts at screening.…”
Section: Discussionmentioning
confidence: 82%
“…The providers cited a lack of confidence due to limited training in screening and treatment of precancerous lesions. These findings are not unique and have been found in surveys of health care providers in similar environments such as Kenya . In addition, limited space and equipment hampered attempts at screening.…”
Section: Discussionmentioning
confidence: 82%
“…They reported that the basic equipment for screening service, including examination table, light source and speculums, were available (94.3%, 81.6% and 97.7%, respectively). Contrary to these findings, inadequate infrastructures and insufficient basic equipment and supplies are repeatedly reported to be among the challenges to cervical cancer screening in resource limited settings (13,14).…”
Section: Discussionmentioning
confidence: 89%
“…Each was involved at different levels of cervical cancer services such as the actual VIA/VILI screening, patient education or filling entry forms (14). Considering the current critical shortage of healthcare professionals in the developing world, this approach in Kenya of training clinicians and non-clinicians in the provision of cervical cancer care services needs to be replicated in other low-resource countries in need of establishing organized and working cervical cancer prevention programs 14 . In Rwanda, community health workers have contributed significantly to decreased maternal morbidity and mortality through increased adherence to prenatal care follow up and increased health facility deliveries (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many of the facilities, only one provider was available to provide family planning and other services, a situation that often lead to providers being overworked under pressure and prone to exhaustion and stress. Manpower shortages in the right number and skill mix has been documented to be a major obstacle in provision of quality health services including family planning in Nigeria and several other similar settings in sub-saharan Africa [24,25].…”
Section: Discussionmentioning
confidence: 99%